SSR marker and morphological trait-based genetic diversity assessment in mori cms based lines and restorers in Indian mustard [Brassica juncea (L.) Czern & Coss] (Journal of Oilseed Brassica, 2025)
Indian mustard is a vital oilseed crop with significant economic and industrial importance. This study aimed to evaluate the genetic diversity among 15 genotypes of Indian mustard (Brassica juncea L.), consisting of 10 Mori CMS lines and 5 restorer lines, using SSR markers and agro-morphological traits. Out of 87 SSR primers screened, 40 showed successful amplification. A total of ninety-five alleles were amplified, with an average of 2.38 alleles per locus. The major allele frequency ranged from 0.30 to 0.93, with an average of 0.63 per SSR locus. The polymorphism information content (PIC) values ranged from 0.12 to 0.67, averaging 0.40, indicating moderate discriminative power. Gene diversity per locus ranged from 0.12 to 0.72, with an average of 0.45. Notably, six SSR markers exhibited PIC values greater than 0.50, demonstrating their effectiveness in differentiating the genotypes. Genetic divergence based on morphological traits was analyzed using Mahalanobis’s D2 statistics. Cluster analysis of SSR profiles, performed with NTSYS software version 2.0, grouped the 15 genotypes into four clusters, while morphological traits analyzed using Torchers method grouped the genotypes into four clusters. Utilizing genotypes from different clusters for hybridization could potentially yield feasible heterotic combinations, contributing to the development of superior cross combinations.